Physical and rheological characterization of carbonated bitumen for paving applications - Apeagyei, Alex K.; Airey, Gordon (Elsevier, 2018)
In the paving industry, current attempts aimed at reducing greenhouse gas emissions have focused on the development of technologies that decrease bitumen viscosity so that asphalt mixtures can be produced at temperatures that are lower than conventional mixing temperature for hot-mix asphalt. This study focuses on the feasibility of producing new lower energy asphalt mixtures using CO2-modified bitumen. Gravimetric sorption techniques were used to establish the kinetics of CO2 diffusion in bitumen at multiple pressures. The rheological properties of the carbonated bitumen were characterized at multiple temperatures and loading frequencies using a dynamic shear rheometer.